Supportive Care and Symptom Management for Patients With Immunoglobulin Light Chain (AL) Amyloidosis - Jensen, Christopher E.; Byku, Mirnela; Hladik, Gerald A.; Jain, Koyal; Traub, Rebecca E.; Tuchman, Sascha A. (Frontiers in Oncology, 2022)
Immunoglobulin light chain (AL) amyloidosis is a disorder of clonal plasma cells characterized by deposition of amyloid fibrils in a variety of tissues, leading to end-organ injury. Renal or cardiac involvement is most common, though any organ outside the central nervous system can develop amyloid deposition, and symptomatic presentations may consequently vary. The variability and subtlety of initial clinical presentations may contribute to delayed diagnoses, and organ involvement is often quite advanced and symptomatic by the time a diagnosis is established. Additionally, while organ function can improve with plasma-cell-directed therapy, such improvement lags behind hematologic response. Consequently, highly effective supportive care, including symptom management, is essential to improve quality of life and to maximize both tolerance of therapy and likelihood of survival. Considering the systemic nature of the disease, close collaboration between clinicians is essential for effective management.